(untitled) (Khairulummah, 2022)
Ibne Miskawayh was born in famous Ray city of Iran (born 930 A.D.-died 1030 A.D.).He was a famous philosopher, a great historian and religious scholar of 10th century. In his quest for knowledge he became a secretary, and later served as librarian and various other positions with Buyid rulers, both in Ray and Baghdad. Both Persia and Iraq were the most important centers of learning during the Abbasid period (750–1258 CE).His scholastic works became models for generations of that time. Both Persians, Arabs Romans and even the whole of central Asians. Later on Islamic thinkers and generations had to cite him as authority in philosophical and historical works. His works included history, poetry, philosophy, ethics and the study of alchemy. They are literary master pieces of his times. His most notable contributions, however, were in ethics and history. His legendary moral discourse Tahdhīb al-akhlāq, is said to be influenced by the neo-platonic concept, is considered one of the best statements of Islamic philosophy. The Islamic philosopher Naṣīr al-Dīn Ṭūsī (died 1274) modelled his Akhlāq Naṣīrī (“The Naṣīrī Ethics”) on the Tahdhīb al-akhlāq. His universal history Kitāb tajarīb al-umam wa ta’aqub al-ḥimam was noted for its use of all available sources and greatly stimulated the development of Islamic historiography. Ibne Miskawayh blended the classical Arabic literary culture of adab and philosophical thought processes of Greek and Romans. Thus Miskawayh is known to be harmonizing not only the various trends within Greek ancient philosophy, but also made an attempt to rationalize the Islamic tradition through philosophical thought processes. This research paper brings out mainly an objective investigation of the Islamic moral dimensions of Ibne Miskawayh works and its utilitarian importance for present young generation and contemporary Academics.